INFLUENCE OF TERRAIN AND RATIONAL WAYS OF USING TERRAIN IN ARCHITECTURAL DESIGN - Vahobov I. S. (Modern conceptions of processes and technology: problems, states and perspectives)
Relief also affects the resistance of buildings to natural disasters such as earthquakes, floods and landslides. Architects must consider local terrain when designing buildings to ensure their safety and durability. Studying the influence of relief on architecture allows us to better understand the principles of human interaction with the environment and create a harmonious and functional space.
Keywords: инновации; уникальность; дизайн; архитектура; учет; инженеры; innovation; accounting; engineering; design; engineers; architecture; uniqueness; рельеф местности; методы решения; инженерия; buildings; terrain; natural environment; solution methods; types of relief; architectural solutions; technical aspects; natural factors; environmental friendliness; successful projects; natural features; строения; природное окружение; виды рельефа; архитектурные решения; технические аспекты; природные факторы; экологическая чистота; успешные проекты; природные особенности